Pelatihan Skrining Gizi bagi Pengelola Usaha Kesehatan Sekolah di SMP Negeri 13 Kota Semarang - Gregorius Tsiompah (Universitas Tidar, 2023)
Adolescence is a period of transition or transition from childhood to adulthood. At that time, teenagers are often overwhelmed by a lot of ignorance about their development which can cause their own problems. One of the health problems that are most often experienced by adolescents today is the triple burden of malnutrition, namely undernutrition, excess nutrition (obesity), and iron deficiency anemia. Anthropometric nutritional status measurement is one way of early detection of growth retardation for children. Routinely under the coordination of the Puskesmas, measuring the weight and or height of new school children is one of the screening tools for children's health. Insufficient height is assumed to be the result of long-term malnutrition that can interfere with student learning achievement and low body resistance to disease and child mortality. One of the efforts to minimize this problem is to monitor nutritional status early, especially in the school environment. The School Health Effort (SHE) is the spearhead of the “health promotion school” effort. With the training on nutritional status assessment for the UKS managers/officers of the State Junior High School (SMPN) 13 Semarang City, it can help partners find out an early picture of the nutritional status of students. The method of implementing nutrition screening training activities consists of 4 stages, namely planning, implementation assisted by powerpoint media, and anthropometric measurement tools, evaluation (pre-test and post-test), and reflection. The training participants were students from SHE management, totaling 30 people. Based on the results of the evaluation by comparing the pre-test and post-test results, the participants after being given training understood and were able to practice anthropometric measurements of weight and height, and were able to determine nutritional status by looking at the BMI/U index table.